Grazing rest during spring regreening period promotes the ecological restoration of degraded alpine meadow vegetation through enhanced plant photosynthesis and respiration - Liu, Ying (Frontiers in Plant Science, 2022)
Grazing rest during the spring regreening period is the most economical and feasible measure for the ecological restoration of degraded alpine meadows, and has been widely popularized and applied in China. The aim of the present study was to undertake a comparative analysis of the effects of grazing rest on the ecological restoration of degraded alpine meadows by plant photosynthesis and respiration. Coverage, height, ground biomass, belowground biomass of degraded alpine meadow vegetation, net photosynthetic rate, stomatal conductance, transpiration rate, intercellular CO2 concentration, chlorophyll fluorescence parameters, relative chlorophyll content, respiration rate, metabolite content, leaf relative water content, and related mineral element content of the dominant grass Elymus nutans Griseb. were measured in degraded alpine grassland with different grazing rest years. The results show that grazing rest during the spring regreening period promoted ecological restoration of degraded alpine meadows by enhancing photosynthesis and respiration of the dominant grass E. nutans Griseb. Grazing rest enhanced photosynthesis in dominant grass by increasing metabolites related to the Calvin cycle, chlorophyll content, leaf relative water content, and related mineral element contents. Grazing at rest enhanced the respiration of dominant grass by increasing metabolites related to the TCA cycle, leaf relative water content, and related mineral element content. This positive effect gradually became stable with increasing years of grazing rest. Our results provide a fundamental basis for the popularization and application of grazing rest during the spring regreening period on degraded Tibetan Plateau grasslands.